Strategi Penguatan Modal Sosial untuk Keberlanjutan Desa Wisata Kandri - Prima Sari, Ninda; Abduk Malik (Pusat Riset dan Inovasi Nasional, 2024)
The sustainability of tourism villages is a significant issue amidst the dynamics of tourism and social change. One of the key elements influencing this sustainability is social capital, which encompasses trust, networks, and collective norms within the community. Kandri Village is an education and culture-based tourism village that relies on the active involvement of the community in destination management and development. This research aims to analyze strategies for strengthening social capital in supporting the sustainability of Kandri Tourism Village. The study employs a qualitative approach with a case study design using interview, observation, and documentacion techniques. Interviews were conducted with various informants, including the Head of Pokdarwis (Tourism Awareness Group), community leaders, Pokdarwis members, business actors, village officials, and the general public. Data were analyzed thematically to identify strategic patterns and forms of social collaboration that emerged. The research findings indicate that social capital is strengthened through regular training for Pokdarwis members, cross-group mutual cooperation (gotong royong), participation in community forums, partnerships with government and universities, and collaboration in managing education and religious-based tourism destinations. Social capital in the form of trust, mutual cooperation, and solidarity becomes the main strength, maintaining harmony among residents and ensuring the continuity of tourism activities. This study concludes that strategies for strengthening social capital play a significant role in supporting the sustainability of tourism villages across social, economic, and institutional dimensions.